Exploring Identity in Kashmiri Trauma Narratives: A Study of "The Half Mother" by Shahnaz Bashir - Abbas, Ghulam; Malik, Moazzam Ali (Pakistan Languages and Humanities Review, 2023)
The current study explores how "The Half Mother" presents the impact of the Kashmir conflict on the fragmented identities of the characters and demonstrates how their trauma has individual and collective facets. By delving into this inquiry through the analysis of the text of "The Half Mother" the objective of this research is not solely to enhance the comprehension of the interplay between trauma and identity within the novel but also to contribute to the broader conversation concerning the profound reverberations of trauma on human self-perception and the fabric of society. Guided by LaCapra’s (2001) trauma theory, the nuanced textual analysis helps us to understand how trauma shapes individual and collective identities and how the characters in "The Half Mother" negotiate their identities in the backdrop of the conflict-ridden Kashmir region. The study challenges the Eurocentric understanding of trauma and draws the attention of the civilized world to the extent of traumatic upheaval experienced by marginalized third-world nations.